(untitled) (Ra. Revista de Arquitectura, 2020)
The steady erosion of the material base of architectural design and construction has been principally caused by economic considerations. As a result, the very moral, intellectual and substantive foundations of architecture have been eroded. This demise parallels developments in other fields of human culture. The cumulative effect of this erosion is the “construction” of thin layers of fiction that consolidate states of false consciousness. Over centuries, architecture has both been coopted and allowed itself to become the servant of collective fictions. With climate change, the next layer of fiction to be superimposed on this cultural veneer is that of “nature”.